Corporate tax competition and the decline of public investment - Pedro Gomes; Francois Pouget (Center for Economic Studies and ifo Institute (CESifo), 2008)
The government's choices of the corporate tax rate and public investment are interdependent. In particular, they both respond positively to the other. Therefore, international tax competition not only drives corporate tax rates to lower levels but might also affect negatively the stock of public capital. We build a general equilibrium model that illustrates the relation between the two variables. We then add an element of international tax competition. Our simulations show that when international tax competition drives the statutory tax rate down from 45% to 30%, public investment is reduced by 0.4% of output at the steady state. The short run effect is three times higher. The second part of our study displays an empirical analysis that corroborates the main outcome of the model. We estimate two policy functions for 21 OECD countries and find that corporate tax rate and public investment are endogenous. More precisely, a decline of 15% in the corporate tax rate reduces public investment by 0.6% to 1.1% of GDP. We also find evidence that international competition operates on both policy tools.
Keywords: H0; H26; H54; 330; Tax competition; corporate tax; public investment; public capital; Unternehmensbesteuerung; Steuerwettbewerb; Öffentliche Investition; Infrastrukturinvestition; Allgemeines Gleichgewicht; OECD-Staaten